2016
DOI: 10.1002/cjce.22752
|View full text |Cite
|
Sign up to set email alerts
|

Advanced treatment of actual textile dye wastewater by Fenton‐flocculation process

Abstract: To improve the performance of actual textile dye wastewater treatment, an advanced treatment combining the Fenton and flocculation processes was developed. The parameters affecting decolorization in the Fenton-flocculation process, including initial pH, H 2 O 2 dosage, Fe 2þ dosage, reaction temperature, reaction time, and flocculant dosage, were examined. With the optimal Fenton-flocculation condition parameters, more than 95 % COD removal, 99 % colour removal, and 99 % turbidity removal were obtained. UV-vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 37 publications
2
22
0
Order By: Relevance
“…Besides, the peaks at the binding energy of 529.0 eV in Figure 4B 1 and 532.6 eV in Figure 4C 3 were both due to the adsorbed O on the surface of the samples. In Figure 4C 4 , the peaks at about 36.3 eV and 35.2 eV of W 4f 7/2 suggest the formation of W-O and W-S bindings. S 2p spectra in the obtained samples ( Figure 4A 2 ,C 2 ) could be deconvoluted into three pairs of peaks (S 2p 3/2 , S 2p 1/2 ), corresponding to MoS 2 , MoS x , and W-S-Mo respectively.…”
Section: The Elemental Chemical States Analysis Of Samplesmentioning
confidence: 96%
See 1 more Smart Citation
“…Besides, the peaks at the binding energy of 529.0 eV in Figure 4B 1 and 532.6 eV in Figure 4C 3 were both due to the adsorbed O on the surface of the samples. In Figure 4C 4 , the peaks at about 36.3 eV and 35.2 eV of W 4f 7/2 suggest the formation of W-O and W-S bindings. S 2p spectra in the obtained samples ( Figure 4A 2 ,C 2 ) could be deconvoluted into three pairs of peaks (S 2p 3/2 , S 2p 1/2 ), corresponding to MoS 2 , MoS x , and W-S-Mo respectively.…”
Section: The Elemental Chemical States Analysis Of Samplesmentioning
confidence: 96%
“…Therefore, it is meaningful to treat wastewater containing MB [3]. At present, there are many physical, chemical, and biological methods used in the treatment of organic dye wastewater, such as flocculation precipitation [4], hydrogen peroxide treatment [5], and photo electrocatalytic degradation [6,7]. Chemical adsorption is a method of adsorbing nonionic organic refractory compounds in dye wastewater [8].…”
Section: Introductionmentioning
confidence: 99%
“…The optimal CPCTS-g-P (CTA-DMDAAC) dosages for different Chl-a contents were investigated, and corresponding experimental data were obtained. The R 2 of the linear fit equation was 0.502, thereby indicating that CPCTS-g-P (CTA-DMDAAC) dosage had a certain relative relationship with Chl-a content [43]. Under some conditions, it can be used to predict the optimal CPCTS-g-P (CTA-DMDAAC) dosage for obtaining the maximum Chl-a removal rate [44,45].…”
Section: Effect Of G Value On Flocculation Propertiesmentioning
confidence: 98%
“…An advanced treatment method combining the Fenton and flocculation processes was used for dye wastewater treatment (Xiao et al, 2017). The results showed that, more than 95% COD, 99% color, and 99% turbidity, were removed from dye wastewater.…”
Section: Pharmaceutical Wastewatermentioning
confidence: 99%